Pengenalan Huruf Hijaiyah Pada Anak Usia Dini Melalui Aplikasi Game Puzzle Berbasis Android di TPA Darul Farhan Palangkaraya - Khairul Sadi; Ikbal Lupariq (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
In this community service activity by lecturers and students of IAIN Palangkaraya, the aim is to conduct implementation related to the introduction of hijaiyah letters in early childhood through an Android-based puzzle game application at TPA Darul Farhan. Palangkaraya, at TPA Darul Farhan, researchers found that it still does not use Android-based media in its learning activities. Researchers offer the use of media in the form of Android-based puzzle game applications in introducing hijaiyah letters in early childhood at TPA Darul Farhan. This research was conducted because of the background of the rampant use of Android by early childhood, which allows them to access something that is not appropriate. So this application is suitable to be taught to early childhood so that they are accustomed to accessing useful things in using their gadgets. The parties involved in this study are us as researchers, early childhood teachers at TPA Darul Farhan. The data collection techniques that researchers use are tutorial and socialization methods. The research was aimed at early childhood at TPA Darul Farhan, aged 4-6 years, with a total of 4 students. The results obtained from this community service were that the students were quite enthusiastic in participating in the implementation of activities and increasing the knowledge, abilities, skills, and abilities of early childhood in recognizing various features in an application and the use of an Android-based puzzle game application.